2018
DOI: 10.1016/j.marpol.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of Marine Stewardship Council (MSC) certification in Russia: Achievements and considerations

Abstract: A B S T R A C TThe Marine Stewardship Council (MSC) certification program in Russia is now well established and, in addition to fishery clients and stakeholders, involves environmental NGOs and experts familiar with the local management system. The present study aims to analyze the current status of the program and constitutes the first study covering all Russian MSC certifications. Based on certification reports and twenty semi-structured interviews with stakeholders, it was shown that problems with certifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…This label is applied to sustainable capture fisheries industries. As of May 2017, 312 fishing industries in 30 countries have been certified as meeting MSC standards (Lajus et al, 2018). Studies on MSC certification have found that the MSC label positively affects consumer preferences worldwide (Alfnes et al, 2018).…”
Section: Transition Theory and The Role Of Ngosmentioning
confidence: 99%
“…This label is applied to sustainable capture fisheries industries. As of May 2017, 312 fishing industries in 30 countries have been certified as meeting MSC standards (Lajus et al, 2018). Studies on MSC certification have found that the MSC label positively affects consumer preferences worldwide (Alfnes et al, 2018).…”
Section: Transition Theory and The Role Of Ngosmentioning
confidence: 99%
“…Исследователи выделяют несколько основных факторов, влияющих на внедрение подобных институтов в сфере устойчивого природопользования [22]. Вопервых, это рыночные характеристики компании.…”
Section: система морского попечительского совета (Msc)unclassified
“…One of the ways in which IUU fish can enter legal supply chains is through weak monitoring and controls during landing in ports. Salmon fisheries in the Sea of Okhotsk in the Russia Far East, an area historically associated with high levels of IUU fishing (Lajus et al, 2018), have taken steps to ensure that MSC certified salmon caught in Russian waters and landed in Russian ports could be assured as coming from a certified sustainable and legal origin. As an additional assurance that all data gaps are closed, the conformity assessment body (CAB) performing the audit evaluated both the fishery and the first buyers with CoC certificates.…”
Section: Closing the Gap: Strengthening Chain Of Custody From Port To Processormentioning
confidence: 99%